Development and application of a silicon coordinate detectors - Kulibaba, V.I.; Maslov, N.I.; Naumov, S.V.; Ovchinnik, V.D.; Potin, S.M.; Starodubtsev, A.F. (Вопросы атомной науки и техники, 2003)
An attempt is made to consider general approach and the techniques for development, investigation and application of multichannel silicon coordinate detectors. Зроблено спробу розглянути загальні підходи і методи розвитку, дослідження і застосування багатоканальних кремнієвих детекторів. Сделана попытка рассмотреть общие подходы и методы развития, исследования и применения многоканальных кремниевых детекторов.